«Kor langt skal det vera?»: Eit essay om å arrangera essaykurs - Moss, Bodil (Nordic Journal of Information Literacy in Higher Education, 2025)
The Writing Centre at The Western Norway University of Applied Sciences (HVL) offers an essay course as an optional 40-hour module which is integrated in the development program for basic competence in University Pedagogy. We initiated the course because faculty teachers supervising students writing an academic essay as a bachelor's assignment requested training in essay supervision. In this essay, I reflect on the challenges I have faced in the development and implementation of the essay course, above all why some teachers turn out to become so insecure, or so it seems, when faced with open evaluation criteria. What makes this genre so difficult? How can we help teachers become more confident in writing academic essays so that they can guide students in a more productive way in their writing process and assess the essays they write? When we asked the course participants to write their own essays and supervise each other in the writing process during the course seminars, it became clear that they too, just like the students, want clear answers. Many of them tend to ask for ready-made assessment criteria and guidelines for good academic essays – for both students, lecturers and examiners. I suspect that some faculty teachers prefer to operate with templates when giving assignments to students. However, reflections on professional experience, the very hallmark of an academic essay, can rarely be squeezed into a ready-made template. I argue that the insistence on templates actually makes writing, supervising and assessing more challenging.